Early post-stroke cognitive impairment and in-hospital predicting factors among stroke survivors in Ethiopia - Gashaw Walle Ayehu; Fitalew Tadele Admasu; Getachew Yideg Yitbarek; Assefa Agegnehu Teshome; Abraham Tsedalu Amare; Daniel Atlaw; Saurab Sharma; Saurab Sharma (Frontiers in Neurology, 2023)
BackgroundIn low-and middle-income countries, post-stroke cognitive impairment (PSCI) is the least investigated stroke complication that clinically is given little attention. Finding patients who are at high risk of having cognitive problems after a stroke could allow targeted follow-up and help with prognosis discussions, which would then contribute to improved treatment outcomes. The main aim of this study was to determine the incidence and predictors of PSCI among stroke survivors in Northwest Ethiopia.MethodsThe study was a multicenter prospective cohort study. The study participants were 403 stroke survivors who were alive on follow-up after 3 months of stroke onset at the neurology department of three hospitals in Northwest Ethiopia. To investigate the link between the outcome and the explanatory variables, analyses of bivariable and logistic multivariable regression were performed. A value of p of 0.05 or less was regarded as statistically significant, and data were presented as odds ratios and 95% confidence intervals.ResultsThe mean age of the participants was 61.3 years (SD = 0.7), 56% were females, the mean time from symptom onset to hospital arrival was 46 h (SD = 3.32), and the mean National Institute of Health Stroke Scale (NIHSS) score at admission was 14.79 (SD = 0.25). PSCI was observed in 122 patients (30.3%) after 90 days of stroke onset, that is, 83 (20.6%) of female and 39 (9.7%) of male stroke survivors. The result of multivariable logistic regression analysis revealed PSCI was independently associated with age (adjusted OR = 1.04, 95% CI = 1.061–1.981), women (AOR = 1.390, 95% CI = 1.221–2.690), admission modified Rankin scale (mRS) (AOR = 1.629, 95% CI = 1.381–2.037), moderate Glasgow coma scale (GCS) score (AOR = 1.149, 95% CI = 1.402–3.281), and poor GCS score (AOR = 1.632, 95% CI = 1.610–4.361) and stage one (AOR = 1.428, 95% CI = 1.198–2.922) and stage two hypertension (AOR = 1.255, 95% CI = 1.107–2.609).ConclusionNearly one-third of stroke survivors developed PSCI. Moreover, further research is needed with a larger sample size, showing a time trend and longer follow-up duration.